2016
DOI: 10.5935/0103-5053.20160116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trace Elements in Tissues of Fish Species: Multivariate Study and Safety Evaluation

Abstract: Levels of As, Cd, Cr, Cu, Li, Mn, Mo, Ni, Pb, Sb and Se in muscle, gill, stomach, liver, kidney and gonad tissues of six different fish species (Caranx latus, Bagre marinus, Archosargus rhomboidalis, Lutjanus synagris, Scomberomorus cavalla and Sphyraena guachancho) from the Todos os Santos Bay (Bahia State, Brazil) were evaluated. The elements were determined by inductively coupled plasma mass spectrometry (ICP-MS) after wet digestion using reflux system with a cold finger. The detected concentration ranges w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
3
2
2
Order By: Relevance
“…This study recorded variable levels of Se in fish muscles to a maximum of 551.22 μg/kg (T2) ( Table 4 ). A previous study by Silva et al [ 99 ] reported excess Se in fish muscles ranging between 730–2190 μg/kg which was higher than the levels determined in this study ( Table 4 ). Excess level of Se in fish edible parts results in mortality, reproduction failure and reduced growth if consumed frequently by humans [ 100 ], however, small intake is required for regulating thyroid hormone [ 101 ].…”
Section: Resultscontrasting
confidence: 80%
“…This study recorded variable levels of Se in fish muscles to a maximum of 551.22 μg/kg (T2) ( Table 4 ). A previous study by Silva et al [ 99 ] reported excess Se in fish muscles ranging between 730–2190 μg/kg which was higher than the levels determined in this study ( Table 4 ). Excess level of Se in fish edible parts results in mortality, reproduction failure and reduced growth if consumed frequently by humans [ 100 ], however, small intake is required for regulating thyroid hormone [ 101 ].…”
Section: Resultscontrasting
confidence: 80%
“…Compared with other studies, the Pb levels of 0.13 ± 0.12 mg kg À1 in the M. curema obtained in this study were lower than the 0.25 ± 0.05 mg kg À1 reported for Mugil brasilienses from Baia de Todos os Santos, BA, Brazil (Santos et al 2013) and the 0.17 ± 0.09 mg kg À1 in mullet marketed in Palestine (Elnabris et al 2013). A study by Silva et al (2016) found values ranging from 0.019 to 0.022 mg kg À1 in sea bream (Archosargus rhomboidalis) and snapper (L. synagris) marketed in Salvador, BA, Brazil, while in the Mediterranean, Storelli et al (2013) observed Pb concentrations ranging from 0.08 to 0.12 mg kg À1 , considered safe for consumption.…”
Section: Leadcontrasting
confidence: 81%
“…In Brazil, a study conducted by the Food Technical Commission (CTA) in 2013 detected arsenic in samples of tuna fish, whitemouth croaker, and sardines marketed in São Paulo, SP, Brazil, with only 2.5% of the samples below the maximum tolerated values of 1.0 mg kg À1 set by Brazilian Legislation (CTA 2013). Medeiros et al (2012) detected levels of total As between 0.002 and 11.800 mg kg À1 when analyzing fish commercialized in the main market of the city of Niter oi, RJ, Brazil, whereas Silva et al (2016) found between 0.48 and 1.19 mg kg À1 in fish commercialized in Salvador, BA, Brazil. In this study, guachanche barracuda (Sphyraena guachancho) and snapper fish (Lutjanus synagris) exceeded the maximum tolerable limit (MTL) of 1.0 mg kg À1 established by Brazilian Legislation.…”
Section: Arsenicmentioning
confidence: 97%
“…No entanto, o consumo de peixe contaminado pode causar riscos à saúde humana devido às substâncias tóxicas presente em sua composição, como poluentes orgânicos persistentes (Silva, et al, 2016).…”
unclassified